Quality of Life, Risk and Recovery in a National Forensic Mental Health Service: A D-FOREST study from DUNDRUM Hospital. (1st June 2022) - Amin, H.; Edet, I.; Basrak, N.; Crudden, G.; Kennedy, H.; Davoren, M.
Abstract : Introduction: Secure forensic mental health services have a dual role, to treat mental disorder and reduce violent recidivism. Quality of life is a method of assessing an individual patients' perception of their own life and is linked to personal recovery. Placement in secure forensic hospital settings should not be a barrier to achieving meaningful quality of life. The WHO-QuOL measure is a self-rated tool, internationally validated used to measure patients own perception of their quality of life. Objectives: This aim of this study was to assess self-reported quality of life in a complete National cohort of forensic in-patients, and ascertain the associations between quality of life and measures of violence risk, recovery and functioning. Methods: This is a cross sectional study, set in Dundrum Hospital, the site of Ireland's National Forensic Mental Health Service. It therefore includes a complete national cohort of forensic in-patients. The WHO-QuOL was offered to all 95 in-patients in Dundrum Hospital during December 2020 – January 2021, as was PANSS (Positive and Negative Symptoms for Schizophrenia Scale). During the study period the researchers collated the scores from HCR-20 (violence risk), therapeutic programme completion (DUNDRUM-3) and recovery (DUNDRUM-4). Data was gathered as part of the Dundrum Forensic Redevelopment Evaluation Study (D-FOREST). Results: Lower scores on dynamic violence risk, better recovery and functioning scores were associated with higher self-rated quality of life. Conclusions: The quality of life scale was meaningful in a secure forensic hospital setting. Further analysis will test relationships between symptoms, risk and protective factors and global function. Disclosure: No significant relationships.